Yemeni banking system: Critical issues and future recommended strategies - Al-Swidi, A.K.; Mahmood, Rosli (2011)
In the current changing and challenging business environment, banks have been gaining an increasing importance in paving the way for the development processes in any country.Banks, however, bridge the gap between individuals and institutions by mobilizing the money from the individual savers to the borrowing organizations.It has been widely emphasized that the mature and developed banking system of any country results in a significantly growing economy. According to many reports, the Yemeni banking system has been underdeveloped to back up the desired development processes.More seriously, Yemeni savers or customers have no trust to deal with banks in conducting their business transactions.This is reflected by the number of banks accounts holders that does not exceed 4 per cent of the Yemeni population.This paper tried to dig deeply into this situation by highlighting the critical issues related to the Yemeni banking system.As an attempt to identify the reasons behind the weak role of the Yemeni banking system, this paper recommends some strategies that, if adopted, could enhance the capabilities of the Yemeni banks to provide high quality services and foresee the potential business opportunities.